Postnatal depression within the paediatric emergency department. (4th April 2011) - Chin, Lynda; Stock, A; Jordan, B; Bevan, C
Abstract : Introduction: The prevalence of postnatal depression is estimated to be 10–20%, however it is thought that up to 50% of cases go unrecognised in routine clinical practice. There are currently no data regarding incidence of postnatal depression in a paediatric emergency department setting, nor is there at present a systematic way to assess mothers in such an environment – current practice varies between medical staff, and the amount of maternal history obtained is at the discretion of the individual practitioner. Aim: The aim of this study was to determine the incidence of postnatal depression in mothers of infants aged 0–6 months presenting to the emergency department (ED) of a large paediatric hospital, using a well-validated screening tool. Methods: Mothers of patients with a triage category of 3, 4 or 5 (those not acutely unwell) were approached by a researcher while in the waiting room, prior to their child being seen by a doctor. If the mother consented, she was given a questionnaire to complete, comprising a demographics section and the Edinburgh Postnatal Depression Scale, which was then scored by the researcher. Screens with a score of less than 13 were deemed negative, while a score of 13 or higher indicated a positive screen. Screens were also deemed positive if the mother had answered positively to the final question of the EPDS regarding suicidal ideation. If a mother returned a positive screen, the child's treating doctor would be informed (after their initial consultation with the patient) and a social worker assessment offered. Due to this, mothers were only able to be recruited at times when a social worker was available. Results: 238 mothers in total were approached, with 200 completing the questionnaire, 28 refusing and 10 being called through to see a doctor before consent was gained. Of the 200 mothers who completed the questionnaires, 39 returned positive screens (19.5%). Conclusion: The incidence of postnatal depression in the ED setting is relatively high, this should be taken into account when assessing of all young infants in the ED and for the provision of services within ED.